Efektivitas Model Project Based Learning Pada Mata Kuliah Vulkanologi Terhadap Hasil Belajar Mahasiswa - Nusa, Jeilen G. N. (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to determine the effectiveness of learning using the Project-Based Learning (PjBL) Model or project-based learning on student learning outcomes in volcanology courses. This study used a quasi-experimental design with a Nonequivalent (Pretest-Posttest) Control Group Design. The study population was all students who contracted the Volcanology course in the Physics Study Program of the Faculty of Mathematics and Natural Sciences UNIMA for the 2019-2020 Odd Academic Year. The sample used the purposive sampling technique and divided the experimental class and the control class. The research data were collected using a test instrument for the comprehension ability of the material. The results showed that the average student learning outcomes in the experimental class were 89.74%, higher than the control class 72.11%. The results of statistical test analysis, namely t-test, obtained the value of t count 3.80 greater than t table, namely 2.10 with a real level α = 0.05, which means that the effectiveness of project-based learning models (Project Based Learning) on learning outcomes students are better than conventional learning models.